Evaluation of WATSAN technologies in developing countires: development and testing of a diagnostic tool - Roma, Elisa (Cranfield University, 2010)
For decades the problems of access to and sustained use of water and sanitation (WATSAN) technologies in developing countries has dominated the political agendas of international organisations and governments. Despite the significant investments made and the apparent appropriateness of technologies transferred, the effective implementation and sustained use of WATSAN technologies remains a chimera. More importantly, improving access to water and sanitation does not necessarily guarantee the longevity of those systems transferred. Lessons from past interventions suggest that the success of WATSAN interventions depends on the ability of ensuring users‟ broad acceptance of the technologies and sustained used after donor assistance ends. Yet, in the academic literature users‟ feedback and experiences in the post-implementation stage of technologies has received scarce attention. Against this background, this thesis aims to contribute to understanding the dynamics involved in the process of WATSAN technology adoption and sustained use in developing countries by reporting the design and evaluation of a diagnostic post- implementation tool, called RECAP, to address and investigate the problem. This research employs a multiple case study approach to evaluate users‟ post-implementation experience of WATSAN technologies in South Africa and Indonesia. Semi-structured interviews with technology users as well as in depth interviews with local governments and health clinics were conducted in three case studies. By comparing and contrasting technology intended performance and users‟ experiences in the post-implementation stage this study aims to identify potential challenges to technology sustained used. Conclusions relate to the existence of discrepancies between performance and experience, manifested in the post-implementation stage, which suggest the necessity to develop evolving mechanisms to routinely assess users‟ feedbacks of the technologies and assist them with appropriate interventions. Further conclusions relate to the validity, reliability and flexibility of a post-implementation diagnostic tool in investigating user experiences, diagnosing emerging challenges and suggesting remedial intervention to contribute to sustained technology use.
Keywords: water and sanitation; post-implementation evaluation; developing countries